Analisis Efisiensi Pengeluaran Sosial Pemerintah terhadap Pembangunan Manusia di Indonesia : Studi dengan Pendekatan DEA dan Regresi Tobit - Joan Marta; Ziko Fenando Agusto ziko (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the efficiency of government social spending in the education, health, and economic sectors and its impact on human development in Indonesia by employing the Data Envelopment Analysis (DEA) method and Tobit regression to examine the influence of external factors on efficiency. The findings reveal that the efficiency of government social spending varies across provinces, with most provinces recording high efficiency in the education and health sectors, while the economic sector still faces efficiency challenges. Population growth rate and land area were found to have a negative effect on efficiency, as rapid population growth and large territorial size create obstacles in resource allocation and distribution. Conversely, foreign direct investment (FDI) has a positive and significant effect on efficiency in all sectors.